Discourse and indigenous policy during Leguia’s Oncenio - Gonza Castillo, Américo (2020)
This article looks into August B. Leguia’s political discourse on indigenous issues and the actions he undertook from the State apparatus during his 1919-1930 administration – the so-called Oncenio (the Elevenium). The primary sources reviewed at the Archivo General de la Nación (The Nation’s Archives) and the document analysis performed evidenced that Leguia’s political discourse was populistic and that the actions undertaken by his administration meant little to the well-being of indigenous populations.